Role of Vitamin D in Prevention of Food Allergy in Infants - Giannetti, Arianna; Bernardini, Luca; Cangemi, Jessica; Gallucci, Marcella; Masetti, Riccardo; Ricci, Giampaolo (Frontiers in Pediatrics, 2020)
The prevalence of food allergy is increasing over the last decades. The role of vitamin D in the prevention of food allergy has been largely investigated. Its role on the physiology of calcium and bone is known, but calcitriol (active form of the vitamin D) also influences the epithelial cells, T cells, B cells, macrophages, and dendritic cells. Almost all cells of the adaptive immune system express the vitamin D receptor, making them also capable of being vitamin responsive. Specifically considering the potential role of vitamins in food allergy, vitamin D has been shown to affect several mechanisms that promote immunologic tolerance, including the T regulatory cell function and the induction of tolerogenic dendritic cells. The target of our review is to evaluate the role of vitamin D in the prevention of food allergy in children. There are contradictory data on the relationship among the vitamin D deficiency and the developing of food allergy. Some studies associate lower exposure to sunlight to food allergy; on the other hand, further research has found that higher vitamin D levels could increase the likelihood of allergic sensitization and food allergy. Therefore, there is an urgent need for well-planned randomized controlled trials on vitamin D supplementation, with particular regard to the prevention of food allergy. The role of vitamin D beyond bone and calcium metabolism is not fully understood.